Pyogenic hepatic abscess induced secondary to toothpick penetration of stomach - Dev-Aur Chou; Min-Chang Hung; Ji-Ching Lai; Wayne Shih-Wei Huang (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Chou DA, Hung MC, Lai JC, Huang WSW. Pyogenic hepatic abscess induced secondary to toothpick penetration of stomach. Turk J Gastroenterol 2018; 29: 241-2.